Evaluation of Fungicides for the Control of Bakanae Disease of Rice Caused by Fusarium moniliforme (Sheldon) - Hossain, MS; Ali, M Ayub; Mollah, MIU; Khan, MAI; Islam, AKM Sajjadul (Bangladesh Rice Journal, 2015)
Bakanae is one of the major diseases of rice in Bangladesh and causes substantial yield loss. To control the disease eleven fungicides from different fungicidal groups were evaluated for their efficacy against seed-borne fungus, F. moniliforme as seed treatment both in the laboratory and in the seed-bed during 2011 and 2012. In the laboratory the fungicides were evaluated at three concentration levels viz 2.5, 3.0 and 3.5 gm/L/kg seeds. Overall performance of the fungicides was found to be better in suppressing the seed-borne F. monilifome and increasing seed germination. Among the fungicides, Bavistin, Sunphanate, Nativo and Carzeb completely inhibiting the growth of F. moniliformeinvitro condition at their low (2.5 gm/L) concentration. Efficacy of the fungicides reduced to some extent when the treated seeds were washed with fresh water except Bavistin. Maximum (85%) average germination was found in Bavistin and Greenzeb treated seeds. The promising fungicides further evaluated to control seedling infection at low (2.5 gm/L) concentration and resulted significant reduction of bakanae infected seedlings in pot soil and in seed bed. Bangladesh Rice j. 2015, 19(1): 49-55